"For the Creation of Strong Children, Beautiful and Intelligent": Eugenics, Youth, and the Nation in Post‐Revolutionary Mexico City. Issue 3 (12th September 2018) - Orisich, Shari
Abstract: This article examines the link between eugenics, youth, and the nation in Mexico City from 1920‐1940. Eugenicists, far from being a homogenous group, couched their work as a "patriotic duty" and placed proper child development at the forefront of plans for national renovation in the first decades after the revolution. From scientific journals, Pan‐American Congresses, and records from the Juvenile Court in Mexico City, the voices of non‐elite actors like physicians, criminologists, and biologists reveal the transnational dimensions of reform and the local anxieties over the growing youth population in the city. As agents of the state in clinics, schools, and courts, I argue that eugenicists shaped the public discourse on 'proper' childhood and adolescence, and placed families and independent minors migrating to the city under scrutiny when they encountered state institutions. Delinquency was forged in contrast to these new norms, and connected popular classes to social problems like prostitution and begging through what they termed 'bad' inheritance. By placing youth at the center of historical inquiry, we can observe the places and spaces inhabited by eugenics in Mexico and see the social role eugenicists played in shaping everyday lives of people living and working in Mexico City.